Profitability of positive selection technique for seed yam production in Ghana and Nigeria - Jonas Osei-Adu; Robert Aidoo; Simon Cudjoe Fialor; Stella Ama Ennin; Kingsley Osei; Bright Owusu Asante (Cogent Economics & Finance, 2022)
Over the years, the traditional seed system has failed to deliver quality seed yam for propagation. This is due to the high incidence and severity of the yam mosaic virus leading to yield losses of 52.6%-65.4%. The Positive Selection (PS) technique has shown promise as a possible mitigation measure. This study was therefore aimed at evaluating the profitability of seed-yam production through the use of PS technique as a viral mitigation measure. Three hundred and sixty-eight (368) seed yam farmers across Ghana and Nigeria were sampled. Profitability was determined using Return on Investment (ROI) and Benefit Cost Ratio (BCR) analysis. Regression analysis was applied for the determinants. Result from this study indicates that seed yam production is more profitable when the effect of the yam mosaic virus is mitigated using PS technique with a net return of US 3,417.98/ha compared to US 1,795.58/ha for non-use. This implies the use of PS technique can increase seed yam profitability by 26.69%. Sex, farmer experience in yam production, education, migration status, extension contact, off-farm income and use of PS technique were significant determinants of profitability. It is therefore recommended that the PS technique be widely disseminated as a mitigation strategy for the control of the yam mosaic virus disease.
Keywords: 330; Positive selection; Profitability; Returns; Investment and Seed Yam